(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
تم تطوير طريقة طيفية لونية سريعة وسهلة التطبيق لتحديد الهالوبيريدول (Hal) في مستحضراته الصيدلانية باستخدام صباغ الكالكون (Cal)، تعتمد على تشكيل معقد، زوج شاردي بين شرجبة (Hal)، وشرسبة الصبغة(Cal) بلون وردي قابل للاستخلاص بالكلوروفورم في وسط واقي حمضي عند pH = 2.4، امتازت طيوف المعقد المتشكل(Hal-Cal) بقمة امتصاص أعظمية عند طول الموجة 531 نانومتر، وكانت العلاقة ما بين الامتصاصية وتركيز (Hal) طردية خطية، وتحقق قانون بير ضمن مجال للتراكيزما بين 1.20 - 33.83 ميكروغرام/ مل، وبانحراف عياري نسبي مئوي لم يتجاوز %3.85 لأصغر تركيز تم تحديده، وبمعامل امتصاص جزيئي 104 x 2.1817 (mol-1.cm-1. L) وبقيم استرجاعية ما بين %101.67-98.33 من أجل معقد Hal-Cal، استخدمت هذه الطريقة بنجاح في تحديد الهالوبيريدول بشكله النقي، وفي المستحضرات الصيدلانية (مضغوطات ونقط) ولم نلحظ حدوث إعاقة من المواد المساعدة الداخلة في تركيب هذه المستحضرات. امتازت الطريقة المطورة بأنها سهلة وسريعة التطبيق وذات دقة وحساسية كبيرتين. تم إجراء هذا البحث في مختبر أبحاث الكيمياء التحليلية في كلية الصيدلة – جامعة حلب خلال العام الدراسي 2009-2010 This study develops a simple and fast spectrophotometric method for the determination of haloperidol (Hal) in pharmaceutical formulations by using Calcon (Cal). This method is based on the formation of a pink colored ion-pair complex between the cation (Hal) and the anion (Cal), which is extractable with chloroform in an acidic buffer medium at pH 2.4. The spectrum of the resulting complex showed a maximum absorbance at wavelength of 531 nm. We found that the relationship between absorbance and concentration of (Hal) is linear and obeys Beer’s law in the concentration range of 1.20– 33.83 g/mL, with molar absorptivity of 2.1817x104 L. mol-1. cm-1 with relative standard deviation not exceeding 3.85% for the lowest concentration of Hal-Cal. Recoveries were impressive, ranging between 98.33-101.67%. This method was successfully applied for the determination of commercially available haloperidol in pure and in pharmaceutical formulations (tablets and drops), without interference from relevant excipients. This method offers the advantage of being simple, fast and sensitive with good precision and reproducibility.